PERAN PEREMPUAN DALAM MENINGKATKAN PENDAPATAN KELUARGA (STUDI KASUS USAHA KERAJINAN BAMBU DI DESA BARAE KECAMATAN MARIORIWAWO KABUPATEN SOPPENG) - H. Nashar Nashar; Andi Kasirang T. Baso (Jurnal Pallangga Praja (JPP), 2022)
women as one of the human resources in the labor market, especially in Indonesia, have a large contribution,in the sense that the number of women who offer themselves to work is quite large. Women in Barae Villageparticipate especially in fulfilling the economic functions of their families and households. The participationof women workers is closely related to family background, given that the function of the family in decisionmaking is very decisive. It’s just that the value of female labor is sometimes still low, while women also havehousehold obligations that cannot be ignored. This study aims to determine the role of women in bamboomanagement and the contribution of women to family income in Barae Village, Marioriwawo district,soppeng Regency. The study was conducted in Barae Village, Marioriwawo district, soppeng Regencyfrom March to april 2022. The population in the study were women who worked in the bamboo managementindustry and a sample of 36 people. data collection methods are observation and interviews. The dataanalysis used is descriptive and contribution analysis. The results showed that the role of women in bamboo management, from the production process to the marketing of the produce, was carried out by women. Theproducts produced are winnows, rice baskets, and parcel baskets. The contribution of women’s income tofamily income is 24.52%. The total average income obtained based on the results of the analysis is Rp.2,083,889,- per month. for respondents’ income from the sale of woven bamboo products - an average of495,000, - per month.